Substantiation of diagnostic parameters for determining the technical condition of transmission assemblies in trucks - Aulin, Viktor; Hrinkiv, Andriy; Dykha, Aleksandr; Chernovol, Michailo; Lyashuk, Oleg; Lysenko, Sergey (Eastern-European Journal of Enterprise Technologies, 2018)
We have conducted a selection of diagnostic parameters to control technical condition of the gear box. Development of technical operation of transportation vehicles is aimed at examining and predicting a technical condition with the formation of a rational diagnostic base being a key direction. Solving the tasks in a given scientific-technical field was based on the theory of relative sensitivity. This involved a theoretically substantiated relationship between diagnostic parameters and the indicators of reliability for the assemblies of transportation vehicles based on their parametric dependence that we proposed. The implementation of theoretical research was conducted by determining a technical condition based on the express diagnosis of transmission oil in the gear box of the family of trucks KamAZ. We have performed express control and examined the working transmission oil for the following parameters: alkaline number, the content of mechanical impurities, dielectric permittivity. The dependences of their change on the run of transportation vehicles were obtained, as well as the corresponding criteria of sensitivity over different intervals of the run. We selected diagnostic parameters and formed a rational base using the criterion of relative sensitivity, establishing the run and the required diagnostic parameters. Control over diagnostical parameters of the gear box should be executed for the following indicators: the content of mechanical impurities in transmission oil – within intervals of 0…12 and 48…60 thousand km of the run; the dielectric permittivity of oil should be controlled within 48…60 thousand km of the run; the alkaline number of transmission oil should be controlled within 12…24 and 48…60 thousand km of the run of the examined transportation vehicles. Based on the compiled rational diagnostic base, it is possible to run an analysis and predict technical condition of the gear box, as well as establish supporting operations in technical operation.